2008
DOI: 10.1161/circulationaha.107.653576
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Function in Cardiovascular Disease, Part I

Abstract: I n 1616, Sir William Harvey was the first to describe the importance of right ventricular (RV) function in his seminal treatise, De Motu Cordis: "Thus the right ventricle may be said to be made for the sake of transmitting blood through the lungs, not for nourishing them." 1,2 For many years that followed, emphasis in cardiology was placed on left ventricular (LV) physiology, overshadowing the study of the RV. In the first half of the 20th century, the study of RV function was limited to a small group of inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
501
0
21

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,318 publications
(531 citation statements)
references
References 92 publications
9
501
0
21
Order By: Relevance
“…In our study, a higher total bilirubin level was found in patients with thrombocytopenia, which encouraged us to speculate that low platelet counts might reflect RV dysfunction. Previous study has proved that RV failure was a strong marker of cardiovascular morbidity and mortality in patients with heart failure 37. Finally, a decline in platelet counts was considered a sign of hematologic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a higher total bilirubin level was found in patients with thrombocytopenia, which encouraged us to speculate that low platelet counts might reflect RV dysfunction. Previous study has proved that RV failure was a strong marker of cardiovascular morbidity and mortality in patients with heart failure 37. Finally, a decline in platelet counts was considered a sign of hematologic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is evidence that right ventricular dysfunction is correlated with LV dysfunction in patients with DCM 27. We experienced difficulty in RV volumetric and functional assessment because of geometric complexity and asymmetry of the RV 28. Cardiac magnetic resonance imaging might be an option to evaluate RV remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression in DCM affects both ventricles, and right ventricular (RV) dysfunction represents an important adverse prognostic factor 2, 3. Although several clinical trials have demonstrated that left ventricular dysfunction in DCM can be partially reversed by cell therapy 4, 5, 6, 7, no study to date investigated the effects of this approach on RV.…”
Section: Introductionmentioning
confidence: 99%